Disease prevention strategies following flood disasters: A scooping review - Taqiuddin, Muhammad Hafidh; Stephania, Agnes; Wiguna, Ilham; Afriana, Reni; Agustin, Sigit; Liana, Yeni; Pakpahan, Yetty Mardelima Uli; Muthmainnah, Muthmainnah; Trisyani, Yanny; Emaliyawati, Etika (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Floods are a frequent natural disaster that significantly impacts public health, particularly the spread of infectious diseases. Effective health interventions are needed to reduce post-flood health risks. Purpose: To map the literature related to post-flood disease prevention strategies. Method: This scoping review involved five main stages: (1) identifying the research question; (2) identifying relevant studies; (3) selecting studies; (4) recording data; and (5) summarizing and reporting the results. The literature search for this observation was conducted in three databases: the National Library of Indonesia, ScienceDirect, and Google Scholar. The inclusion criteria for articles were published between 2021 and 2025 in English and Indonesian, literature reviews, opinion pieces, editorials, or conference abstracts focused on post-flood disease prevention, the research setting was community-based, participants were health workers, and post-flood outcomes were the primary outcome. Results: Five key themes emerged from the analysis: increasing access to clean water and sanitation, community education, surveillance and rapid response, mental health support, and a multisectoral approach. Integrated and collaborative health interventions have proven crucial in reducing post-flood disease incidence. Conclusion: Despite progress in post-flood health interventions, there are still gaps in research focusing on long-term interventions, vulnerable populations, and multisectoral approaches. Recommendation: Future research should address these aspects to improve the effectiveness of health policies and practices in addressing post-flood health challenges. Keywords: Disease Prevention; Post-Flood Disaster; Strategy. Pendahuluan: Banjir merupakan bencana alam yang sering terjadi dan berdampak signifikan terhadap kesehatan masyarakat, terutama dalam penyebaran penyakit menular. Intervensi kesehatan yang efektif diperlukan untuk mengurangi risiko kesehatan pasca banjir. Tujuan: Untuk memetakan literatur terkait strategi pencegahan penyakit pasca bencana banjir. Metode: Penelitian scoping review yang melibatkan lima tahapan utama: (1) mengidentifikasi pertanyaan penelitian; (2) mengidentifikasi studi yang relevan; (3) pemilihan studi; (4) pencatatan data; (5) merangkum dan melaporkan hasil. Pencarian literatur dalam tinjauan ini dilakukan di 3 database yaitu Perpusnas, ScienceDirect dan Google Scholar. Kriteria inklusi artikel yaitu diterbitkan antara 2021-2025 dalam bahasa Inggris dan Indonesia, literature reviews, opini, editorial, atau abstrak konferensi berfokus pada pencegahan penyakit setelah banjir, setting penelitian di komunitas, partisipan adalah tenaga kesehatan, dan post floods sebagai outcome utama. Hasil: Lima tema utama yang muncul dari analisis adalah peningkatan akses air bersih dan sanitasi, edukasi masyarakat, surveilans dan respons cepat, dukungan kesehatan mental, dan pendekatan multisektoral. Intervensi kesehatan yang terintegrasi dan kolaboratif terbukti penting dalam mengurangi insiden penyakit pasca banjir. Simpulan: Meskipun terdapat kemajuan dalam intervensi kesehatan pasca banjir, masih terdapat kesenjangan dalam penelitian yang berfokus pada intervensi jangka panjang, populasi rentan, dan pendekatan multisektoral. Saran: Penelitian di masa depan perlu memperhatikan aspek-aspek ini untuk meningkatkan efektivitas kebijakan dan praktik kesehatan dalam menghadapi tantangan kesehatan pasca banjir. Kata Kunci: Disease Prevention; Following Flood Disasters; Strategies.